A teoria da instrução de Jerome Bruner aplicada ao aprendizado do arco-íris - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
Physics is usually learned in school by having the students work through physics questions. He retains the information in his memory of it and uses it to address issues without necessarily understanding the theory. It is crucial to consider an alternate teaching paradigm in a scenario where material available outside of the classroom is cheaper, more readily available, and more attractive. In view of this, this work aims to provide a proposal in which the student is the protagonist in his learning process, and experiences other than the already conventional "blackboard and chalk" are included. Through a sequence of activities that take into account how the student portrays his information from him, the student in this proposal develops his own knowledge, without skipping any steps. This educational product was separated into nine ordered and sequential segments to offer learning opportunities, based on the instructional concept of Jerome Bruner and Cruz's theory of the real external knowledge generator. Following methodological implementation, the analysis of the results has shown a noticeably improved comprehension of how students perceive knowledge about how a rainbow works and the most fundamental laws in optics. This assumption is reinforced by the results, which demonstrate that the students used a set of appropriate symbols to describe optical phenomena.
Keywords: Ensino de física; óptica; formação do arco-íris; Teaching physics; optics; rainbow formation; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA